Strategic Agricultural Policies and Fertilizer Subsidies: Driving Business Success in Cianjur's Rice Sector - Rusmayadi, Gusti; Widiyanto, Sigit; Suparwata, Dewa Oka; Wardani, Dini Tri (International Journal of Business, Law, and Education, 2024)
This research investigates the impact of strategic agricultural policies and fertilizer subsidies on the business success of rice farmers in Cianjur, Indonesia. A quantitative approach utilizing cross-sectional survey data from 300 rice farmers was employed. The study explores the demographic profile of respondents, descriptive statistics of key variables, correlations between policy variables and business success indicators, and regression analysis to assess predictors of rice yield. Results indicate a high utilization rate of fertilizer subsidies, positive correlations between subsidy utilization and business success indicators, and significant contributions of access to extension services, credit facilities, and infrastructure improvements to rice yield. The integration of policies in a holistic approach emerged as crucial for enhancing business success and promoting sustainable farming practices. These findings have implications for policymakers in crafting targeted and integrated policies to support agricultural resilience and livelihoods in Cianjur and similar agricultural regions.